Field Dielectric Sensor for Soil Pollution Application. Issue 1 (June 2021) - Ismail, R; Dahim, M; Jaradat, A; Hatamleh, R; Telfah, D; Abuaddous, M; Al-Mattarneh, H
Abstract: This paper presents a new dielectric sensor which could be used for assessment and evaluation of soil pollution in the field. The new device determines the dielectric properties of soil from the measured soil impedances. The dielectric properties used as indirect method to estimate type and pollution content in soil. The new device was calibrated and validated for accurate measurement of soil dielectric properties in the frequency range of 1 kHz to 30 MHz. The new proposed dielectric sensor was used to measure the dielectric properties of clean and contaminated soil. The measured dielectric properties of soil using the proposed sensor could be used to estimate soil moisture content, hydrocarbon diesel and salinity in sand soil. The results also show that the dielectric properties of clay soil were higher than the dielectric properties of san due to existing bound water in clay minerals. Further testing is necessary to evaluate the effects of other parameters such as temperature and various type of soil prior to adopt the sensor for field testing.